2002
DOI: 10.1046/j.1464-410x.2002.03031.x
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral interstitial laser coagulation of the prostate and transurethral microwave thermotherapy vs transurethral resection or incision of the prostate: results of a randomized, controlled study in patients with symptomatic benign prostatic hyperplasia

Abstract: Objective To compare the efficacy and frequency of complications of transurethral interstitial laser coagulation (ILC) and transurethral microwave thermotherapy (TUMT) with transurethral resection or incision of the prostate (TURP/TUIP) in patients with symptomatic benign prostatic hyperplasia (BPH). Patients and methods Forty-eight patients were randomized to undergo ILC, 46 to TUMT and 24 to TURP/ TUIP; they were followed for 6 months and the outcome analysed on an intention-to-treat basis. Results At 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 36 publications
(50 reference statements)
1
46
0
Order By: Relevance
“…A change of 3 points in the IPSS is perceptible to patients. Assuming a Gaussian distribution of IPSS with a standard deviation (SD) of 4, choosing a minimal relevant difference of 3.2, a risk of type 1 error of 0.05 and a risk of type 2 error of 0.10, the sample size was calculated and results suggested that a minimal of 50 patients should be included in each group [20,21] . Data are expressed as mean 8 SD or number of cases (percentage).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A change of 3 points in the IPSS is perceptible to patients. Assuming a Gaussian distribution of IPSS with a standard deviation (SD) of 4, choosing a minimal relevant difference of 3.2, a risk of type 1 error of 0.05 and a risk of type 2 error of 0.10, the sample size was calculated and results suggested that a minimal of 50 patients should be included in each group [20,21] . Data are expressed as mean 8 SD or number of cases (percentage).…”
Section: Discussionmentioning
confidence: 99%
“…This technique usually leads to postoperative complications including acute urinary retention and irritative voiding [24][25][26] because the heat treatment is closely related to postoperative edema which may worsen the obstructive symptoms and result in urinary retention [27] . The median time in which urinary retention resolves is about 45 days following ILC [21] . Some researchers proposed the application of temporary and biodegradable stents following ILC [28] .…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In the short term, minimally invasive surgical therapies such as TUMT have been shown to be less expensive and as effective or less effective than TURP. [21][22][23][24] In contrast, patients choosing a treatment pathway starting with medical therapy and ending with successful TURP or open simple prostatectomy, have the highest lifetime treatment costs. 19,25,26 The evidence supporting these results is not of high-level since only five studies address the longterm cost consequences or cost effectiveness of various BPH treatment alternatives beyond a few years period.…”
Section: Cost Differences Between Various Bph Treatment Optionsmentioning
confidence: 99%
“…Six studies were evaluated involving 540 patients with a median follow-up of 6-12 months (Table 2) [6,7,[9][10][11][12]. The pooled mean urinary symptom score decreased 65% with TUMT and 77% with TURP.…”
Section: Transurethral Microwave Thermotherapymentioning
confidence: 99%